2010
DOI: 10.1039/b926990h
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a water molecule using a mononuclear Mn complex: from Mn-aquo, to Mn-hydroxo, to Mn-oxyl via charge compensation

Abstract: Activation of a water molecule by the electrochemical oxidation of a Mn-aquo complex accompanied by the loss of protons is reported. The sequential (2 × 1 electron/1 proton) and direct (2 electron/2 proton) proton-coupled electrochemical oxidation of a non-porphyrinic six-coordinated Mn(II)OH2 complex into a mononuclear Mn(O) complex is described. The intermediate Mn(III)OH2 and Mn(III)OH complexes are electrochemically prepared and analysed. Complete deprotonation of the coordinated water molecule in the Mn(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 108 publications
9
45
0
Order By: Relevance
“…Key properties are (i) that it can stabilize multiple oxidation states to be accessed over a narrow range of redox potentials. This property is derived from protein/cofactor interactions being able to tune the pK a of cofactor bound water (substrate) molecules allowing sequential H þ release upon each Mn oxidation event; (ii) the possibility that the heterobimetallic cubane allows the formation of an energetically accessible Mn V -oxo or Mn IV -oxyl radical in the transition state [85][86][87][88]; and (iii) that the Mn ions represent trapped valence states of local high-spin states, which magnetically couple together in a precise way in each S-state.…”
Section: Discussionmentioning
confidence: 99%
“…Key properties are (i) that it can stabilize multiple oxidation states to be accessed over a narrow range of redox potentials. This property is derived from protein/cofactor interactions being able to tune the pK a of cofactor bound water (substrate) molecules allowing sequential H þ release upon each Mn oxidation event; (ii) the possibility that the heterobimetallic cubane allows the formation of an energetically accessible Mn V -oxo or Mn IV -oxyl radical in the transition state [85][86][87][88]; and (iii) that the Mn ions represent trapped valence states of local high-spin states, which magnetically couple together in a precise way in each S-state.…”
Section: Discussionmentioning
confidence: 99%
“…15 Model compounds assessing the properties and reactivities of Mn IV -OH and Mn IV =O as well as Fe IV -OH and Fe IV =O species have been reported by several groups. 16,17,18,19,20,21 Que and co-workers have examined Fe complexes that are remarkable for their H-atom abstraction capabilities. 22,23 In some systems, it is possible to resolve the protonation state of oxo bridged species through single-crystal X-ray crystallography 6 where unusually long or short M-O and M-OH bonds have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[70] For OÀO bond formation,t wo routes werep roposed:t he concerted path involves the reaction betweenM n IV -oxy and water, whereas the two-stepp ath involves coordination of the Mn ion to water,w hich can lead to OÀOb ond formation from the MnÀOH bond. [73] In 2015, Gupta et al reported that high oxidation state Mn V =Oe xisted and radicalc oupling for OÀO bond formation was al ikely mechanism during the OER. Dey and coworkers found am ononuclearM n-corrole complex that could catalyzet he OER with fast kinetics.…”
Section: Mononuclear Manganese-based Catalystsmentioning
confidence: 99%
“…also reported that the OÀOb ond formation was formed by Mn IV =Oo rM n III -oxy. [73] In 2015, Gupta et al reported that high oxidation state Mn V =Oe xisted and radicalc oupling for OÀO bond formation was al ikely mechanism during the OER. [74] In 2017, Li et al researched the catalytic mechanismo f [Mn{Py 2 N(tBu) 2 (H 2 O) 2 }] 2 + for the OER.…”
Section: Mononuclear Manganese-based Catalystsmentioning
confidence: 99%